STATUS AND PROSPECTS OF FISH AND FISH PRODUCT MARKETING IN KARNATAKA - B., LOKESH G.; KHIDRAPURE, GAJENDRA (Journal of the Inland Fisheries Society of India, 2021)
The structure and performance of fish and fish products marketing in Karnataka was analysed through a combination of primary and secondary collection of information. Data were obtained from annual reports of fisheries department. Karnataka is one of the most important States contributing 4.75% of India’s total fish production. The contribution of Fisheries Sector to GSDP at current prices during 1993-94 was Rs. 16,316 lakhs and it has increased to Rs. 286273 lakhs in 2012-13. The policy suggestions for further development of fisheries sector are: Strengthening of fish marketing by developing strong marketing networks through Fisheries Corporation’s cold chain; Development of Inland Fisheries by proper incentives to farmers for taking up fish rearing and to strengthen fisheries research and education; Creation of Reservoir Development Authority for better management of the reservoirs; Fish seed rearing may be encouraged by involving private entrepreneurs to use public water body; Use of ICT for Inter connection and co-ordination of fish farms; Promote Ornamental fish production and marketing, and bring comprehensive policy for protecting water resource bodies and their flora and fauna. Key words: Fisheries, policy, inland fisheries, fish products, fish marketing